RECURRENT PERI-OP HAEMATURIA IN REPEAT LOWER SEGMENT CAESAREAN SECTION: an unusual Presentation of Renal Cell Carcinoma in Pregnancy (A Case report with Literature Review) - Hota, Basanta Manjari; Naaz, Nabila; Pujitha, M.; Banoth, Swathi Bai; Basavaih, Prabhakar Gowdar Channa (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Trauma to urinary bladder is the commonest cause of haematuria in repeat lower segment caesarean section. However, recurrent post op haematuria draws the attention to other aetiologies. Case: A 27 year old lady, G2P1L1, post caesarean pregnancy at term gestation, underwent elective caesarean section and tubectomy. She developed haematuria in perioperative period in episodic manner. Abdominal and pelvic ultrasound revealed a solid mass lesion in the upper pole of right kidney of size 5.8x4.6mm, which was confirmed by CECT of abdomen to be renal cell carcinoma. She was managed with radical nephrectomy in the urology centre without any adverse event. This rare presentation of the case and its successful management, prompted us to present this case with available literatures review.
Keywords: Haematuria, Lower, segment, caesarean, renal, pregnancy.